Metabolic reprogramming of macrophages by PKM2 promotes IL-10 production via adenosine - Juliana Escher Toller-Kawahisa; Paula Ramos Viacava; Eva Margareta Palsson-McDermott; Daniele Carvalho Nascimento; Mariana Patricia Cervantes-Silva; Shane Myles O'Carroll; Alessia Zotta; Luis Eduardo Alves Damasceno; Gabriel Azevedo Públio; Pedro Forti; João Paulo Mesquita Luiz; Bruno Marcel Silva de Melo; et al. (Cell Reports)
Summary: Macrophages play a crucial role in immune responses and undergo metabolic reprogramming to fulfill their functions. The tetramerization of the glycolytic enzyme pyruvate kinase M2 (PKM2) induces the production of the anti-inflammatory cytokine interleukin (IL)-10 in vivo, but the underlying mechanism remains elusive. Here, we report that PKM2 activation with the pharmacological agent TEPP-46 increases IL-10 production in LPS-activated macrophages by metabolic reprogramming, leading to the production and release of ATP from glycolysis. The effect of TEPP-46 is abolished in PKM2-deficient macrophages. Extracellular ATP is converted into adenosine by ectonucleotidases that activate adenosine receptor A2a (A2aR) to enhance IL-10 production. Interestingly, IL-10 production induced by PKM2 activation is associated with improved mitochondrial health. Our results identify adenosine derived from glycolytic ATP as a driver of IL-10 production, highlighting the role of tetrameric PKM2 in regulating glycolysis to promote IL-10 production.